LEO constellation design for regional coverage based on the safety of van allen belt radiation. Issue 3 (September 2018) - Kohani, Saeid; Zong, Peng
Abstract: Space radiation in the Van Allen radiation belt reduces the life time of the satellite. Also deployment in LEO, below the Van Allen belts, reduces the delay associated with sending signals to and from satellites. In these type orbits one can improve the design of satellite constellations by devising ways to reduce the number of satellites in constellations. Such an optimized design lowers the cost of construction and launch. This paper analyzes ways to optimize the design of constellations to lower costs. The timing of the launching and replacing of unhealthy satellites to avoid breakdown of a constellation also can have a major cost impact and also improve the level of system. Thus an improved method to design LEO constellations for communication and navigation is proposed in this paper, it takes coverage capability and precession into consideration to create an improved design for a LEO constellation, The issue of optimizing the number of satellites and other effective ways to improve an LEO constellation design is discussed and analyzed. It provides the optimal solutions for enhancing the constellation capability for either communication and navigation. The simulation results confirm the performance of the proposed algorithm and indicates that it is feasible and effective.